Iban women development and empowerment: role of Iban women as breadwinner in the family - Taasim, Shairil Izwan; Rosli, Anita; Md Saad, Juniza; Daud, Adrian; Robin, Tunung (The Malaysian Association of Consumer and Family Economics, 2023)
Dual-income families are growing in the new millennium due to high living costs. Nowadays, women also play the role of breadwinners in the family, being in the workforce or working part-time. Many Iban working women and full-time homemakers are involved in side-income activities to earn additional income for the family. It is often involved them performing several activities to earn additional income for their family. This study investigates the role of Iban women as breadwinners involved in side-income activities in Sarawak by identifying types of side-income activities and barriers to side-income activities, thus proposing relevant training or programs to support and encourage their involvement in side-income activities. The study employed a descriptive research design, and 325 Iban women participated in this survey. Based on the survey, there are three main side-income activities among respondents, i.e., farming, handicraft making, and business. However, there are three main barriers to conducting side-income activities, i.e., a need for knowledge and skills in specific fields, marketing and promotional problems, and financial constraints. Based on the problems, three suggestions have been proposed by a high percentage of respondents, i.e., marketing and promotional assistance, business and entrepreneurship courses, and financial assistance. The selection of appropriate training and programs is crucial as the training and program should be need-driven oriented because only some of the training or programs could fit the needs of Iban women. The side-income activities among Iban women benefit the family, develop Iban society, and encourage Iban women's development and empowerment in Sarawak.